Risk Assessment for Nuclear Terrorism Probability and Its Application on a Hypothetical Nuclear Facility - Kot, Joeun L; Harris, Jason T (Health physics (1958), 2025)
Radiation protection contains the key elements of nuclear safety and security. Despite the overlap between nuclear safety and security, their objectives differ fundamentally, focusing on unintentional accidents and intentional malicious events, respectively. As such, the Potential Facility Risk Index (PFRI), originally created for security purposes, has evolved into an approach that combines conventional probabilistic risk assessment (PRA), which is a widely employed method to evaluate the safety risks of nuclear facilities. This research has developed a risk assessment model within the PFRI framework to calculate the probability of nuclear terrorism. Three essential components of the model are integrated: an analysis of historical nuclear terrorism data to determine an initial threat frequency; the target-specific factor using analytical hierarchy process (AHP) target attractiveness analysis; and the adversary motivation factor based on site-specific social influences from the Profiles of Individual Radicalization in the United States (PIRUS) dataset. Applied to a hypothetical nuclear facility, the model produces a nuclear terrorism probability of 8.97 × 10 -3 y - 1 . The systematic methodology proposed in the study enables the derivation of nuclear terrorism probability with results in the same risk unit as safety risk assessment. This method allows decision makers to seamlessly incorporate nuclear safety and security risk assessments, offering a comprehensive perspective. Consequently, it enriches comprehension of nuclear facility risks and establishes the groundwork for future advancements.